Participatory video for inclusive agricultural research for development - Koningstein, Manon; Azadegan, Shadi; Dror, Iddo (2016)
Successful agricultural research for development (AR4D) should go beyond generation of quantitative research findings, and ensure these findings feed into context-relevant development interventions. An understanding of the context in which the research takes place is therefore essential for AR4D, and ought to include all groups that make up the research context in the process: include their voices, opinions, needs and ideas and look for ways to communicate these to a variety of audiences.